The Contribution Of Civic Education Teachers In Preventing Moral Decline Among Students At Stabat State Vocational High School 1 In The Digital Age - Wais Al Qarni, Muhammad; Miswar (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Moral decline has become a growing concern in education during the digital era, particularly among adolescents in vocational high schools. This study aims to explore the contributions of Islamic Religious Education (PAI) teachers in addressing students’ moral decline at SMK Negeri 1 Stabat. Employing a qualitative approach, data were collected through observation, interviews with 5 PAI teachers and 8 students, and documentation. The data were analyzed using techniques of reduction, presentation, and conclusion drawing. The findings reveal that PAI teachers contribute significantly by habituating students to pray before and after lessons, embedding Islamic values in digital behavior, teaching critical digital literacy, encouraging ethical and productive use of technology, promoting tolerance, and fostering responsibility. A key finding highlights that consistent religious habituation combined with digital literacy education helps build students’ ethical resilience. Obstacles faced include limited student understanding of social media ethics and low parental engagement. Overall, PAI teachers serve as moral guides who integrate religious principles with digital awareness to counteract moral degradation in the digital age.